PENGEMBANGAN METODOLOGI PEMBELAJARAN PAI MELALUI TEORI PEMROSESAN INFORMASI DAN TEORI NEUROSCIENCE - Suprapto, Anas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
his article examines the development of Islamic education learning methodology with two theories, namely the theory of information processing and neuroscience theory. The article concludes that the development of Islamic education learning methodology through the first theory is done by the teacher should present PAI learning materials in a creative and interesting, so that students will be stimulated and liked the material taught by the teacher. Meanwhile, with the second theory done by means teachers must first know and understand the performance of the human brain, after that then, PAI teacher can use a variety of learning models of Islamic education attractive to students or learners. Both of these theories have great benefits for the learning of Islamic education that had been there